Ump postgraduate students excelled at the international conference on food properties 2014 - Jolius, Gimbun (Penerbit UMP, 2014)
January 25th 2014, Kuala Lumpur - UMP's postgraduate students showed their worldclass performance when their papers received best paper awards at the International Conference on Food Properties 2014 (iCFP2014).